The urban-rural wage gap in Germany - Udo Brixy; Stephan Brunow; Carsten Ochsen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
We compare real wage differences between centralized and peripheral areas and highly centralized and peripheral areas using vast information of German administrative data that contains more than 2.8 Million individuals and 660,000 firms. We provide substantial empirical evidence that most of the wage gaps can be explained by differences in endowments of individual and firm characteristics, particularly when unobserved individual and firm heterogeneity is appropriately accounted for. Our interpretation is that the selectivity of workers and firms in space explains most of the real wage gap between peripheral and (highly) centralized regions, and returns to characteristics are honoured rather equally in all regional types. – – Wir vergleichen die Reallohnunterschiede zwischen zentralisierten und peripheren Gebieten sowie zwischen hochzentralisierten und peripheren Gebieten anhand umfangreicher deutscher Verwaltungsdaten, die mehr als 2,8 Millionen Personen und 660.000 Unternehmen umfassen. Die Analysen liefern umfangreiche empirische Belege dafür, dass die meisten Lohnunterschiede durch Unterschiede in der Ausstattung mit individuellen und betrieblichen Merkmalen erklärt werden können, insbesondere wenn unbeobachtete individuelle und betriebliche Heterogenität angemessen berücksichtigt wird. Unsere Interpretation ist, dass die räumliche Selektivität von Arbeitnehmern und Unternehmen den größten Teil des Reallohngefälles zwischen peripheren und (stark) zentralisierten Regionen erklärt, und dass die Erträge aus den Merkmalen in allen Regionstypen in etwa gleich hoch sind.
Keywords: J31; R12; 330; Firm characteristics; Oaxaca-Blinder decomposition; Rural-urban wage gap; wage equation